Analysis of the Needs for the Development of Mobile Learning Applications with the SDG's Zero Hunger Theme in Elementary Schools (LPPM Universitas Buana Perjungan Karawang, 2025)
In this modern era, human needs are affected by various activities that often damage the environment and disrupt the balance between population and natural resources, thus threatening the availability of food and nutrition. Indonesia faces a significant hunger problem, ranking third highest in Southeast Asia in 2021. The SDG's by the United Nations targets to end hunger, improve food security and balanced nutrition. Learning that contains SDG's needs to be applied from an early age, especially since children step on elementary school. In teaching something, especially to elementary school children, it is necessary to use media as a communication tool, the SDG's based Mobile Learning application is considered effective in teaching these values in an interesting and interactive way. Therefore, this study focuses on analyzing the needs for the development of Mobile Learning applications containing the Sustainable Development Goals (SDG's) theme of Zero Hunger for elementary school students. This study uses a qualitative descriptive method, collecting data through documentation studies and interviews with educators in Ciamis Regency, Tasikmalaya Regency, and Tasikmalaya City. The results of the interview show that the use of digital media in the form of Mobile Learning applications in learning is welcomed by educators and students, especially visual and audio-visual media. However, knowledge about the SDG's and Zero Hunger theme is still lacking among educators and learners. In the development of an application, it is expected to be able to explain the concept of the SDG's and the Zero Hunger theme in detail and easy to understand, with content that includes E-Modules, E-LKPD, assessments, and additional features such as games to attract students' interest. The designed app should also pay attention to an attractive design that is easy for children to use. This research provides guidance for learning media developers and encourages innovations in technology-based learning methods that can be widely applied.